Perancangan ulang kemasan Susu Kedelai Bu Kati dengan metode Quality Function Deployment dan Geneva Emotion Wheel - Chriswandari, Verena Asri; Hadisantono; Hanandoko, Theodorus B.; Dewa, Parama Kartika (Universitas Atma Jaya Yogyakarta, 2025)
Bu Kati soy milk, an MSME in Kudus that was established in 2015, experienced a decline in sales due to unattractive packaging, easy to leak, and product durability of only one day at room temperature. This study aims to increase consumer interest and extend the product's shelf life so that it can be consumed longer. The problem solving was carried out by combining the Quality Function Deployment (QFD) method to design a packaging design that suits consumer desires, and the Geneva Emotion Wheel (GEW) method to measure consumer emotions towards old and new packaging. From the design results, three designs with bottle sizes of 250 ml, 300 ml, and 350 ml were produced. The 3rd design with a bottle size of 250 ml was chosen because it was considered the most appropriate by consumers. The comparison between the old packaging and the newly designed packaging showed an increase of more than 25% in consumer interest, indicating that the new packaging was more in line with their desires. The new packaging also extended the product's shelf life to two days at room temperature, meeting the established success criteria. In addition, evaluation using the Geneva Emotion Wheel (GEW) method showed an increase in positive emotions and a decrease in negative emotions, indicating an increase in consumer interest in Bu Kati's soy milk products.